Identification of Salmonella Pullorum Factors Affecting Immune Reaction in Macrophages from the Avian Host - Xiao Fei; Qiuchun Li; Xinan Jiao; John Elmerdahl Olsen (Microbiology Spectrum, 2023)
ABSTRACT The host-specific Salmonella serovar S. Pullorum (SP) modulates the chicken immune response to a Th2-biased response associated with persistent infection. This is different from the Th1-biased immune response induced by the genetically close serovar, S. Enteritidis (SE). Based on core genome differences between SP and SE, we used three complementary bioinformatics approaches to identify SP genes, which may be important for stimulation of the immune response. Defined mutants were constructed in selected genes, and the infection potential and ability of mutants to stimulate cytokine production in avian derived HD11 macrophages were determined. Deletion of large genomic regions unique to SP did not change infection potential nor immune stimulation significantly. Mutants in genes with conserved single nucleotide polymorphisms (SNPs) between the two serovars in the region 100 bp upstream of the start codon (conserved upstream SNPs [CuSNPs]) such as sseE, osmB, tolQ, a putative immune antigen, and a putative persistent infection factor, exhibited differences in induction of inflammatory cytokines compared to wild-type SP, suggesting a possible role of these CuSNPs in immune regulation. Single nucleotide SP mutants correcting for the CuSNP difference were constructed in the upstream region of sifA and pipA. The SNP corrected pipA mutant expressed pipA at a higher level than the wild-type SP strain, and the mutant differentially caused upregulation of proinflammatory cytokines. It suggests that this CuSNP is important for the suppression of proinflammatory responses. In conclusion, this study has identified putative immune stimulating factors of relevance to the difference in infection dynamics between SP and SE in avian macrophages. IMPORTANCE Salmonella Pullorum is host specific to avian species, where it causes life-threatening infection in young birds. It is unknown why it is host restricted and causes systemic disease, rather than gastroenteritis normally seen with Salmonella. In the present study, we identified genes and single nucleotide polymorphisms (SNPs; relative to the broad-host-range type Salmonella Enteritidis), which affected survival and immune induction in macrophages from hens suggesting a role in development of the host specific infection. Further studies of such genes may enable understanding of which genetic factors determine the development of host specific infection by S. Pullorum. In this study, we developed an in silico approach to predict candidate genes and SNPs for development of the host-specific infection and the specific induction of immunity associated with this infection. This study flow can be used in similar studies in other clades of bacteria.